Innovation through cooperation : the emergence of an idea economy - Weiers, Georg (Management for Professionals,, 2014)
Many people have great ideas. Without the necessary skills and means most never get to realize them. If they could cooperate with competent firms and entrepreneurs together both could achieve much and this is increasingly happening. Mechanisms are being established making a division of labour between inventors and implementers a reality. This is changing the nature of innovation from an internal R&D, or purely entrepreneurial attempt, to a more cooperative innovation. An Idea Economy emerges, where anyone has the possibility to profit from their ideas, and everyone will benefit from more and better innovation. This book presents us the emergence and structure of the Idea Economy by extending the seminal concepts of Entrepreneurial Society and Open Innovation. Part I describes the big picture on how innovation is evolving, where we are today, and what an Idea Economy will look like. Part II points the way forward, discussing in detail on how cooperation in the innovation process works, and why this is only recently becoming possible.